ENGAGING SECONDARY SCHOOL STUDENTS IN A NARRATIVE WRITING BASED DIGITAL STORYTELLING - Rena Ayu Putri; Abd.Rahman; Triana Kartika Santi; St.Shabibatul Rohmah (RADJA PUBLIKA, 2023)
Internet activities are ICT (Information and Communication Technology) that provide students with the opportunity to learn storytelling through digital media that are presented engagingly and contribute directly to developing storytelling skills. The study used a collaborative classroom activity study design, in which researchers and teachers collaborate to conduct the study. The study followed the steps of educational behavior research: planning, implementation, observation, and reflection. Research data was collected through several means, including student essay sheets, questionnaires, and observation sheets. The subjects of this study were her 30 students of class XI MA. The average score obtained during the preliminary survey was 62. This score increased to 75 in Cycle 1. In Cycle 2, the mean value obtained increased again to 80.5. We highly recommend using digital storytelling to improve your storytelling skills.